Formation Mechanism of Water Chemical Compositions in the Lower Reaches of Dusitu River, China - Zhang, H.B.; Qian, H.; Li, P.Y.; Wu, J.H. (Asian Journal of Chemistry, 2011)
The objective of this paper is to find out the factors causing river water chemical compositions changes in the lower reaches of Dusitu river. River water samples and groundwater samples were collected and analyzed for chemical and isotopic indices. The relationships between water chemical characteristics and geological situation, river flow and hydrogeology conditions were discussed in the study. The results show that: (1) the river flow increases firstly and then decreases along flow path, (2) the d18O and dD in river water decrease in certain degree with flow growth, but increase significantly with flow decreasing, (3) the TDS change and content change of each component increase along flow direction in the same flow, but more stable than the above parameters, (4) the corresponding hydrochemistry types of river water change from Cl·SO4-Na to SO4·Cl-Na influenced strongly by the changes mentioned before. Based on these understanding, we divided the middle and lower Dusitu River into three sub-reaches. This paper discussed the formation mechanisms of river water chemical compositions on every reach by mass balance model, saturation index and isotope fractionation. It is concluded that the formation mechanism on river water chemical composition is in difference each other taken from different reaches in Dusitu river. In its middle reach, the mixing process between river water and groundwater, dissolution of gypsum and halite and the precipitation of calcite play major roles in chemical composition forming process. In the lower river, evaporation, concentration and mixing action are the key factors to impact the formation mechanism, especially evaporation, its proportion obtained about 28.05 % according to the calculated result from isotopic data.